Successful proof of the 'two-stage strategy' for major burn wound repair. Issue 3 (July 2020) - Greenwood, John E.; Damkat-Thomas, Lindsay; Schmitt, Brad; Dearman, Bronwyn
Highlights: Survival of a 95% TBSA burn by immediate burn excision. Synthetic Dermal Matrix applied to allow time for Composite Cultured Skin production. First human patient experience with using Composite Cultured Skin to cover 42% TBSA. Short inpatient stay (249 days) followed by independent living in the community. Abstract: In 2004, in response to inadequacies in wound management techniques employed in the management of massive burns and the consequent high mortality and morbidity, a two stage strategy was conceived to reduce the traditional reliance on autograft, where donor sites were scarce, or absent. Over the next 14 years, two products were developed based in a novel, biodegradable polyurethane foam – a Biodegradable Temporising Matrix (BTM) and an autologous, bilayer (dermis and epidermis) Composite Cultured Skin (CCS). Following immediate burn escharectomy, the 1st stage of the strategy (either at the same operation or a few days later) would involve BTM implantation into the resultant wounds and harvesting of a small autograft for keratinocyte and fibroblast isolation for culture and CCS production. The 2nd stage, five weeks later, would involve delamination of the BTM and the application of the prepared CCS to the BTM 'neo-dermis'. The two stages together designed to reduce the requirement for autograft to the small piece harvested to provide the cells for CCS production. At the end of 2018, an adult male with 95% TBSA burns (85% full-thickness) and significant smoke inhalation was received and was the first to undergo the 'two-stage strategy'. His treatment course and outcome are described herein.